Research engagement by British early-career practitioners in nephrology: a multidisciplinary survey. Issue 12 (14th December 2022) - Bottomley, Matthew J; Beckwith, Hannah; McMahon, Aisling; Nation, Michael; Wheeler, David C; Greenwood, Sharlene; Hughes, Jeremy; Sheerin, Neil S
Abstract : Objectives: To establish barriers and motivators underlying research engagement among early-career practitioners in nephrology across the UK, in order to guide potential interventions to enhance research involvement in renal units. Design: Cross-sectional online survey employing a range of free-text, Likert scale and binomial/multiple-choice responses, distributed via mailing lists and social media. Topics covered research experience, research involvement and barriers, impact of COVID-19 and strategies to improve research engagement. Thematic analysis was used to assess free-text responses. Setting: Renal units throughout the UK. Participants: Non-consultant healthcare staff self-identifying as working in nephrology were included (n=211), with responses from non-UK respondents or consultant nephrologists excluded (n=12). Results: Responses were received from across the multidisciplinary team (physicians (n=83) and nurses (n=83)) and other allied health professionals (n=45). Most were aware of ongoing local research, but under half of them were actively involved. Multivariate analysis indicated employment as a physician, protected time for research activity and provision of appropriate training were associated with greater research experience and output. There was general enthusiasm to undertake research, but perceived barriers included insufficient staffing, lack of time, funding and encouragement. COVID-19 was felt to have further impacted negatively upon opportunities. Among the suggested strategies to promote engagement, mentorship and an online research resource were felt to be of most interest. Conclusions: In the first survey of this type in nephrology, we demonstrate differences across the multidisciplinary spectrum in perceived research experience and accessibility, which have been worsened by COVID-19. Our findings will guide strategies to broaden engagement in early-career practitioners and serve as a baseline to assess the impact of these interventions.